Membrane fouling behaviors in a full-scale zero liquid discharge system for cold-rolling wastewater brine treatment: A comprehensive analysis on multiple membrane processes. (1st November 2022) - Wang, Hailan; Dai, Ruobin; Wang, Lingna; Wang, Xueye; Wang, Zhiwei
Highlights: Membrane fouling in a ZLD system was investigated for multiple NF & RO steps. A correlation between water quality and membrane fouling behavior was unraveled. The membrane fouling behaviors varied along the flow direction in the ZLD system. The 2nd pass RO process was subject to severe aluminum-silica scaling. The aromatic substances and TPHs were universally present on various membranes. Abstract: The challenge of water scarcity drives zero liquid discharge (ZLD) treatment to maximize reuse of industrial wastewater. Deciphering the characteristics and mechanisms of membrane fouling in the membrane-based ZLD system is crucial for the development of effective fouling control strategies. However, current studies only focused on the membrane fouling of single step, lacking in-depth understanding on the ZLD systems using multiple membrane processes. Herein, membrane fouling characteristics and mechanisms in a full-scale ZLD system for cold-rolling wastewater brine treatment were investigated via a comprehensive analysis on multiple nanofiltration (NF) and reverse osmosis (RO) membrane processes. The membrane fouling behaviors showed distinct characteristics along the wastewater flow direction in the ZLD system. Increasing amounts of foulants were deposited on the membrane surfaces with the sequence of the 1st pass RO, 1st stage NF, and 2nd stage NF processes. The organic fouling and silica scaling were more intensive in the 1st stage NF and 2nd stage NF for treating the brine of the 1st pass RO, as the foulants were rejected and concentrated by previous membrane processes. Severe inorganic fouling, containing amorphous SiO2, Al2 O3, and Al2 SiO5, occurred on the membrane surface of the 2nd pass RO membrane, due to the recirculated high-concentration silica, high water recovery, and concentration polarization. For the 3rd pass RO process, both the amounts of organic and inorganic foulants decreased dramatically, due to the low foulant concentration in its influent. This work provides a comprehensive understanding of membrane fouling in a membrane-based ZLD system, facilitating the development of membrane fouling control strategies for multiple membrane processes. Graphical abstract: Image, graphical abstract